Modeling and Distribution Laws of Drilling Force for Staggered Teeth BTA Deep Hole Drill. (9th October 2018) - Li, Xubo; Zheng, Jianming; Li, Yan; Kong, Lingfei; Shi, Weichao; Guo, Bian
Abstract : The boring and trepanning association (BTA) deep hole drilling is a typical self-guiding machining method. The drilling force and its distribution laws along the cutting radius directly affect the stability of drilling and the quality of machined hole. Based on the oblique cutting theory, a novel drilling force model is developed to predict the thrust and torque for staggered teeth BTA deep hole drill with variable geometries. Using the constraint relationships between the cutting force components and cutting angles, combined with the measured drilling force during the drill entrance, the parameters of the model including normal shear angle, normal friction angle and shear stress involved in the cutting force coefficients along the cutting radius, and the axial and circumferential friction coefficients between the guide pads and the hole wall are obtained. The model-predicted drilling force is validated by experimental results.